Por uma teoria da norma administrativa sancionatória : o regime jurídico-administrativo brasileiro e a incidência da teoria das restrições aos direitos fundamentais - Curvelo, Alexandre Schubert (2012)
The present work aims to study the legal regime of the Brazilian administrative law, setting new mode of approach, from the (new) vision of administrative law and its normative structure eminently constitutional, for, from this, view the new administrative penalty from new principles. Demonstrating that the legal restriction of fundamental rights is an important corner for sanctioning administrative law-in particular to be seen what would be the norm and typical administrative rule which could eventually be considered atypical. In the first chapter in an analytical part, it is a reconstruction of the historical formation of the French administrative law, pointing out the major historical moments that passed by the discipline that the legal system, naming, including the major doctrinal theses erected there. By then, a succinct analysis of the history and training of administrative law systems in the German and Italian, aiming for an equal, ideas for the formation of administrative law in Brazil. Settled such premises, administrative law was revisited in the Brazilian system, from its formation to the present, pointing out the important elements of their training. In the second chapter, established the legal and administrative, on the French model, also in this same line of analysis, develops an approach to demonstrate on pillars which formed such a regime, emphasizing the principles of separation of judicial and administrative authority and the principle of legality. By then went on to discuss the legal and administrative Brazil, emphasizing at the outset, the necessary deconstruction of the argument that the principles of supremacy of public interest and the unavailability of public interest over the private sector constituted the basis of our legal and administrative. The historic position in this direction, as shown, is not retaining legal and administrative arrangements in Brazil. Thus, the public interest, historically identified as being particularly distinctive element of the scheme, grants in favor of the principle of human dignity, even so we could recognize, in the second chapter, the applicability of the Theory of Constraint fundamental rights to our penalties. Immediately thereafter, the third chapter, the subjects were faced with the principle of legality administrative of legality in criminal law, is still talked about the administrative rule and its main characteristics. From this relational models were demonstrated many of the standard administrative law, protecting the central issue in its unbroken line of conduct. Finally, it was the analysis of the standard more effectively incompatible with the Brazilian administrative level, which is the norm of administrative misconduct. Several reasons I the misconduct to the administrative sphere, starting with the content of their LIA, in at least three devices. Demonstrated the formal charge and substantial the unconstitutionality of the LIA, also demonstrated, the legal bond that links the legal and administrative restrictions on the theory of rights, and the whole scope of analysis by unveiling assurance mechanisms for administrative law penalties